Parenting Patterns of Working Parents at Home and Working Parents Outside the Home in Formation of Children's Character During the Covid-19 Pandemic: Pola Asuh Orang Tua Pekerja Di Rumah Dan Orang Tua Pekerja di Luar Rumah Dalam Pembentukan Karakter Anak Selama Pandemi Covid-19 - Ayu Retno Duwi Prima Yanti; Feri Tirtoni (Academia Open, 2022)
This study aims to determine the parenting pattern of working parents at home and working parents outside the home in the formation of children's character during the Covid-19 pandemic and to determine the effect of parenting patterns of working parents at home and working parents outside the home in character building. children during the Covid-19 pandemic. The research method used is descriptive-qualitative research. The subjects of this study were the parents of 5th grade elementary school children. The object of this research is parenting style. The method used in collecting data is observation and interviews. The results of the study indicate that there are differences in parenting patterns that cause differences in the character of children. From the results of the study, it is known that many parents educate their children with their different parenting patterns which causes the formation of character in children is also different. In educating, guiding children, appropriate parenting patterns are needed so that the formation of children's character can be in accordance with what parents want.